2023
DOI: 10.1037/tra0001197
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and depression residual symptoms among veterans and service members who completed a 3-week cognitive processing therapy-based intensive treatment program.

Abstract: Objective. While previous studies have documented that evidence-based treatments for posttraumatic stress disorder (PTSD) are efficacious, treatment completers often continue to experience residual symptoms. However, no studies to date have assessed residual symptoms following intensive treatment programs (ITPs) for PTSD, which combine evidence-based PTSD treatment along with adjunctive interventions. The present study examined residual symptoms of PTSD and depression in 482 veterans and service members who co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…Understanding environmental impacts on the persistence of symptoms could be an important endeavor in intensive and residential treatment settings. Overall, the consistency in results between the current study and that of Kovacevic et al (2023) provides corroborating evidence of symptoms most likely to persist following intensive PTSD treatments.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Understanding environmental impacts on the persistence of symptoms could be an important endeavor in intensive and residential treatment settings. Overall, the consistency in results between the current study and that of Kovacevic et al (2023) provides corroborating evidence of symptoms most likely to persist following intensive PTSD treatments.…”
Section: Discussionsupporting
confidence: 77%
“…A series of binary logistic regressions examined the effects of clinically significant change on each residual PTSD (i.e., PCL-M) and depression (i.e., PHQ-8) symptom at posttreatment. Given the number of logistic regression tests, Hochberg's step-up procedure (Hochberg, 1988) was applied to reduce Type I error, mirroring prior research on residual symptoms (e.g., Kovacevic et al, 2023). Since data were collected each week in the program, missing data were handled by last observation carried forward (LOCF).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that this may lead to an impaired feedback regulation in the immune activation in the long run and contribute to stress-related pathology ( Raison and Miller, 2003 ). Interestingly, a number of prior studies have found that after successful treatment, residual symptoms in the hyperarousal cluster of PTSD, for example insomnia, were the most common remaining PTSD symptoms after treatment ( Kovacevic et al, 2022 ; Schnurr and Lunney, 2019 ). As PTSD patients are often predisposed to overreact to subsequent stressors, thereby making them more vulnerable to events ( Kendall-Tackett, 2000 ), it may be important to test the hypothesis of whether these residual symptoms, which frequently remain after successful therapy, are associated with increases in the inflammatory system or with changes in the sympathetic nervous system or HPA axis.…”
Section: Discussionmentioning
confidence: 99%